Exploring the combined effects of sleep apnea and APOE-e4 on biomarkers of Alzheimer’s disease - Turner, Arlener D.; Locklear, Clarence E.; Oruru, Daisha; Briggs, Anthony Q.; Bubu, Omonigho M.; Seixas, Azizi (Frontiers in Aging Neuroscience, 2023)
Objective We determined the interactive associations of apolipoprotein e4 (APOE-e4), and obstructive sleep apnea (OSA) on biomarkers of Alzheimer’s disease and examined for racial/ethnic differences of this association. Methods We used data from the National Alzheimer’s Coordinating Center Uniform Dataset (NACC UDS). All participants undergo annual observations, including demographic survey, battery of neuropsychological tests, blood draw (with genotyping), and a clinical evaluation with medical and cognitive/dementia status assessment, while a subset of participants have cerebrospinal fluid (CSF) biomarkers and neuroimaging data. Biomarkers of AD were characterized as the presence of abnormally low amyloid in CSF, via validated Aβ42 cut off protocols, and total segmented hippocampal volume, and volume of white matter hyper intensities (WMH). While clinical markers (to preview cognitive relationships) were characterized via the Montreal Cognitive Assessment (MOCA). Results Biomarker and clinical marker data were derived from 1,387 participants at baseline (mean age = 69.73 ± 8.32; 58.6% female; 13.7% Black/African American), 18.4% of the sample had sleep apnea, and 37.9% were APOE-e4 carriers. Our results confirmed previous reports that OSA and APOE-e4 were independently associated with AD through abnormal levels of amyloid (F(1,306) = 4.27; p = 0.040; F(1,285) = 60.88; p < 0.000, respectively), WMH volume (F(1,306) = 4.27; p = 0.040; F(1,285) = 60.88; p < 0.000, respectively), and MOCA scores (F(1,306) = 4.27; p = 0.040; F(1,285) = 60.88; p < 0.000, respectively). No significant interaction between OSA and APOE-e4 relative to amyloid emerged, however, race stratified analyses indicated the interaction of OSA and APOE-e4 and was significantly associated with WMH and hippocampal volume in Black/African American, but not white participants. Conclusion OSA and APOE-e4 are interactively associated with WHM in Black/African Americans. This interaction may partially explicate increased levels of risk in this population.